2016
DOI: 10.1007/s12105-016-0776-8
|View full text |Cite
|
Sign up to set email alerts
|

TILs in Head and Neck Cancer: Ready for Clinical Implementation and Why (Not)?

Abstract: The assessment of tumor infiltrating lymphocytes (TILs) has recently emerged as a prognostic biomarker in several solid tumors. Quantification and subtyping of TILs reflects the immune response in the tumor microenvironment, contributing to either tumoral immune attack or escape and thereby affecting outcome. Despite the growing evidence of its value as prognosticator, TILs analysis has not yet found its way to daily clinical practice. The aim of this review is to evaluate whether the current knowledge on TILs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 66 publications
5
64
2
Order By: Relevance
“…Numerous studies have defined the prognostic benefit of specific lymphocyte compartments in HNSCC . In HPV‐OPC, enrichment for CD4 + , CD8 + , and PD1 + tumor infiltrating lymphocytes have been associated with improved prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have defined the prognostic benefit of specific lymphocyte compartments in HNSCC . In HPV‐OPC, enrichment for CD4 + , CD8 + , and PD1 + tumor infiltrating lymphocytes have been associated with improved prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…These HPV-related tumors typically arise in the oropharynx, are found in younger, never-smokers and are associated with better prognosis. Following Wolf’s description in 1986 of improved outcome in tumors with increased lymphocyte infiltration in a small cohort of patients with oral cavity squamous cell carcinoma [223], many studies have described immune cell infiltrates in head and neck squamous cell carcinoma and correlated these with outcome [224226]. While the presence of TILs has generally been associated with improved prognosis, differences have been reported according to anatomic sub-site, tumor compartment (intra-tumoral vs. stromal) and importantly in HPV-positive (HPV + ) compared to HPV-negative (HPV − ) head and neck squamous cell carcinomas.…”
Section: Tils In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
“…As discussed in a recent review [224], TILs in head and neck squamous cell carcinomas may not yet be ready for implementation as a clinical biomarker. Studies evaluating TILs in head and neck squamous cell carcinomas have been limited by small cohort sizes, retrospective approaches, inclusion of heterogeneous populations, univariate analyses, and lack of standardized methodology for TIL quantification.…”
Section: Tils In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
“…Studies performed on large cohorts of patients found the presence of high amounts of tumor‐infiltrating T lymphocytes to be a major predictor of favorable clinical outcome in the case of several tumor types . The prognostic importance of other immune cell types, among others, B lymphocytes, dendritic cells, and regulatory T cells (Tregs) was also demonstrated in some tumor locations, including head and neck cancers . Furthermore, evidence accumulating from both experimental and clinical studies supports the importance of immune reactions in influencing the effects of various types of cancer immunotherapy and also other, non‐immune‐based modalities as chemotherapy, radiotherapy, or targeted therapy .…”
Section: Introductionmentioning
confidence: 96%
“…13,14 The prognostic importance of other immune cell types, among others, B lymphocytes, dendritic cells, and regulatory T cells (Tregs) was also demonstrated in some tumor locations, including head and neck cancers. [15][16][17][18][19][20][21][22] Furthermore, evidence accumulating from both experimental and clinical studies supports the importance of immune reactions in influencing the effects of various types of cancer immunotherapy and also other, non-immune-based modalities as chemotherapy, radiotherapy, or targeted therapy. [23][24][25] These therapies can affect the immune system in many ways which, in turn, may contribute to the success of the therapeutic agents, 23 and evaluation of the components of immune infiltrate was found useful in predicting the efficacy of the treatment and disease outcome in patients with colorectal, breast, or lung cancer.…”
Section: Introductionmentioning
confidence: 99%